El impacto de la ingeniería de sistemas y las soluciones SAP en el sector de las telecomunicaciones - Huaytalla Bazalar, Bento Oversize (2022)
A systems engineer graduated from the University of Lima is aware that, by acquiring theoretical and practical knowledge during the years of study of the career; has the potential and profile to meet different professional challenges, either in different technical branches or in business management. It is thanks to the fact that in our house of studies is profiled and educated to provide solutions based on information and communication technologies, encourages proactivity and continuous learning to improve technical and management skills; prioritizing ethical, social and professional responsibilities, I have met great professional challenges. Based on these pillars formed in my university life, I began my professional development in 2012 when I joined the payroll of a leading company in the telecommunications sector; starting here is a line of professional development from an analyst position, where I consolidate my theoretical knowledge about the ERP SAP. Thanks to my good performance, and after 10 years, I occupy a managerial position aligned to the academic area of "Business Engineering" providing solutions to business processes and polishing my soft skills and financial and budgetary management on expenses and investments of my management with a strategic role in the company. The journey has not been easy, but thanks to my good professional performance and the implementation of my academic training as a Systems Engineer at the University of Lima I have managed to make a career line within one of the leading companies in the telecommunications sector and I have learned that with effort, dedication and determination you can go far, and that the technological curiosity that is fostered within the classroom is the basis for not stagnate in a technological world in constant evolution.